Self-Efficacy and Employability Among Higher Education Students: A Systematic Review of Empirical Studies (2015–2025) - Earlene Tania Rahma; Olievia Prabandini Mulyana; Mary Loi A. Sibucao (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Employability has become an important concern in higher education due to increasing labor market uncertainty and competitive employment demands. Although previous studies have examined the relationship between self-efficacy and employability, findings remain fragmented across different forms of self-efficacy and educational contexts. Therefore, this study aimed to systematically review empirical evidence on the role of self-efficacy in students' employability development. This review followed the PRISMA 2020 guidelines and analyzed studies published between 2015 and 2025 indexed in the Scopus database. Of the 317 identified articles, 12 studies met the inclusion criteria. The findings indicate that self-efficacy was consistently found to contribute to students’ employability both directly and indirectly through mediating factors such as career adaptability, emotional intelligence, achievement motivation, and learning engagement. Various forms of self-efficacy, including career decision-making self-efficacy, academic self-efficacy, social self-efficacy, and general self-efficacy, were also found to support employability development. In addition, educational support and experiential learning environments were identified as important contextual factors supporting students' employability development. This review highlights the importance of strengthening students’ self-efficacy to support career readiness and employability development in higher education contexts.